The association between fetal renal artery indices in late pregnancy and birth weight in gestational diabetes mellitus: A cohort study - Ashraf Sadat Jamal; Mahsa Naemi; Laleh Eslamian; Vajiheh Marsoosi; Maryam Moshfeghi; Maryam Nurzadeh; Taraneh Geran; Marjan Ghaemi; Leila Zanbagh (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Estimation of the fetal birth weight and diagnosis of small for gestational age in the fetuses of women with gestational diabetes mellitus (GDM) are currently imprecise. Objective: We aimed to evaluate the association between fetal renal artery Doppler indices and neonatal birth weight in women with GDM in late pregnancy. Materials and Methods: This cohort study recruited 246 pregnant women from Shariati Hospital in Tehran, Iran, in two GDM and healthy control groups. Participants underwent weekly Doppler ultrasounds in the late pregnancy period (37-40 wk) to determine the Doppler indices of the umbilical artery, middle cerebral, and renal arteries. Fetal growth indices including biparietal diameter, abdominal circumference, head circumference, and femur length were also recorded and compared between the two groups. Results: Fetal growth indices and estimated fetal weight were not significantly different between the two groups. Neonatal birth weight was significantly higher in the GDM group (p < 0.01). The GDM group had significantly higher renal artery indices (resistance index: p = 0.01, pulsatility index [PI]: p = 0.03, and systolic/diastolic ratio [S/D]: p = 0.01) compared to the control group. Also, there was an inverse linear correlation between umbilical indices and birth weight (PI: p = 0.01, S/D: p < 0.01), and between renal artery indices and birth weight (resistance index: p = 0.02, PI: p = 0.01, and S/D: p = 0.03). In the control group, only umbilical artery PI had an inverse linear correlation with birth weight (p = 0.03) and there was no correlation between renal artery indices and birth weight. Conclusion: Using Doppler hemodynamic indices of the renal artery in late pregnancy in women with GDM can be helpful for early detection of hypoxic fetuses, who are at risk of being small for gestational age or having intrauterine growth restriction, even when of normal weight.